Pengembangan LKPD Berbasis Gamifikasi untuk Materi Sistem Gerak Manusia di Kelas XI SMA Negeri 1 Medan - Gres Anjelia Sembiring; Ahmad Shafwan S. Pulungan (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2026)
Biology learning on the Human Movement System still relies on conventional media that are less interactive, causing low student motivation and suboptimal learning outcomes. This study aimed to develop a gamification-based Student Worksheet on the Human Movement System material that is feasible, practical, and effective in improving learning motivation and outcomes of Grade XI students at SMA Negeri 1 Medan. This study used the Research and Development method with the 4D model comprising the Define, Design, Develop, and Disseminate stages. Data were collected through validation questionnaires, teacher and student response questionnaires, motivation questionnaires based on the ARCS model, and pretest-posttest instruments. Feasibility and practicality were analyzed using descriptive percentage analysis, while improvement was analyzed using the Normalized Gain formula. The Student Worksheet obtained material expert validation of 94.64% and design expert validation of 85%, both categorized as highly feasible. Teacher response practicality reached 96.67%, categorized as very practical. The N-Gain scores were 0.79 for learning motivation and 0.81 for learning outcomes, both categorized as high. These results conclude that the gamification-based Student Worksheet is feasible, practical, and effective. This study contributes to innovative Biology instructional media development by demonstrating that gamification elements promote active and student-centered learning in secondary education.